Teaching descriptive-text writing through flannel doll for eight grade students of Junior High School - Anggraini Wulansari (Universitas PGRI Madiun, 2019)
The purposes of this research are to describe the procedure and the strengths and weaknesses of teaching descriptive-text writing through flannel doll for eight grade students of SMPN 1 Maospati. The research uses qualitative as the approach. The design of this research is descriptive research. This research covers of eight grade students of SMPN 1 Maospati. The sample of the research is 30 students of 8I grade which consist of fifteen male and fifteen female. This sample is chosen by purposive sampling. The technique of analyzing data is compiling data, disassembling, reassembling, interpreting, and concluding. The result of the research are: (1) The procedure of “Teaching Descriptive-Text Writing through Flannel Doll for Eight Grade Students of SMPN 1 Maospati” consists of preparation and presentation done by the teacher. These preparation activities includes preparing the Syllabus, RPP, lesson plan, flannel doll, then preparing the classroom into five groups in break time. The presentation activities include pre-activities, whilst-activities, and post-activities. Pre-activities include greeting, checking attendance, and giving apperception and motivation by showing flannel doll. Whilst-activities include giving explanation (modeling) about descriptive text, joint construction of descriptive text about flannel doll (show how to planning and drafting with students), independent construction of descriptive text about each group’ flannel doll (the steps are planning, drafting (writing), revising, editing, and final version (publishing). Post-activities include review and conclude the material. (2) The strengths are flannel doll make the students are enthusiastic, interested in English lesson, happy, active, enjoy, helpful, and easier in writing descriptive text, flannel doll increase the students’ vocabulary and understanding in writing descriptive text, the using of flannel doll in descriptive text writing is suitable for eight grade students of SMPN 1 Maospati, guiding and explaining writing step and the using of editing and revising checklist is helpful for the students in writing descriptive text activity. While the weaknesses are the process of making six flannel dolls need more time, flannel doll will easily dirty if it is not in good hands, some students still crowded in the class, and some students confused to describe the unfamiliar color and the size of the doll’s clothes.